Alcohol consumption during prohibition. by Jeffrey A. Miron and Jeffrey Zwiebel - Miron, Jeffrey A.; Zwiebel, Jeffrey (American Economic Review, 1991)
tag=1 data=Alcohol consumption during prohibition. by Jeffrey A. Miron and Jeffrey Zwiebel tag=2 data=Miron, Jeffrey A.%Zwiebel, Jeffrey tag=3 data=The American Economic Review, tag=4 data=81 tag=5 data=2 tag=6 data=May 1991 tag=7 data=242-247. tag=8 data=ALCOHOL%DRUGS tag=10 data=The burgeoning debate over drug legalisation in the United States has drawn renewed attention to the nation's experience with Prohibition. tag=11 data=1991/3/9 tag=12 data=91/0780 tag=13 data=CAB